2014
DOI: 10.1007/s11033-014-3270-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neurofilament light chain (NFL) mRNA levels in prediabetic peripheral neuropathy

Abstract: Evidence suggests that peripheral nerve injury occurs during the early stages of disease with mild glycemic dysregulation. Two proteins, neuron-specific enolase (NSE) and neurofilament light chain (NFL), have been examined previously as possible markers of neuronal damage in the pathophysiology of neuropathies. Herein, we aimed to determine the potential value of circulatory NSE and NFL mRNA levels in prediabetic patients and in those with peripheral neuropathy. This prospective clinical study included 45 pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…Recently, another study showed that the mRNA levels of NfL (also known as NEFL) in the blood of individuals with impaired glucose tolerance displayed a positive correlation with the severity of DPN [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another study showed that the mRNA levels of NfL (also known as NEFL) in the blood of individuals with impaired glucose tolerance displayed a positive correlation with the severity of DPN [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in individuals with diabetic retinopathy, whole blood mRNA levels of rhodopsin have been shown to reflect a benefit in differentiating the stages of the disease [ 14 ]. Recently, another study showed that the mRNA levels of NfL (also known as NEFL ) in the blood of individuals with impaired glucose tolerance displayed a positive correlation with the severity of DPN [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limited sample size does not allow for reliable estimation of the amount of deviation from normal individuals, particularly beyond the 90th percentile. This model did not account for potential comorbidities associated with older age (e.g., cardiovascular disease, 41 diabetes 42 , and cognitive impairment) or other factors that could impact NfL levels (e.g., body weight, normalized brain volume). This model was developed using NfL data analyzed on the SIMOA platform, and additional investigation is needed to understand generalizability to data collected on other platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma NfL levels were also inversely associated with brain glucose metabolism, longitudinally in the highly characterized Alzheimer’s Disease Neuroimaging Initiative (ADNI cohort) ( 23 ). A previous report indicated a positive correlation between NfL mRNA levels and Douleur Neuropathique 4 questionnaire score in pre-diabetic patients, indicating an early detection marker of pre-diabetic peripheral neuropathy ( 24 ). Therefore, plasma levels of NfL may be an attractive indicator of neurodegeneration in people with different glycaemic status.…”
Section: Introductionmentioning
confidence: 92%